PWE-070 Intratumoural variability in prostaglandin E2 levels in human colorectal cancer liver metastases is associated with differences in NAD+ levels and expression of NAD+-dependent 15-prostaglandin dehydrogenase. (23rd September 2015) - Young, A L; Hawcroft, G; Chalmers, R; Toogood, G J; Hull, M A
Abstract : Introduction: Cyclooxygenase (COX)-2 (synthesis) and NAD+-dependent 15-prostaglandin (PG) dehydrogenase (15-PGDH; catabolism) are rate-limiting enzymes in control of tissue PGE2 levels. COX-2 and 15-PGDH function may be affected by the tumour micro-environment (eg, hypoxia) leading to changes in local PGE2 concentration and altered cancer cell behaviour. Epithelial-mesenchymal transition (EMT) is believed to be crucial for tumour cell invasion/metastasis. EMT is promoted by PGE2 in several cell types in vitro. We investigated the relationship between PGE2 levels, COX-2 and 15-PGDH expression, and NAD+ levels in human colorectal cancer liver metastases (CRCLM), and the role of hypoxia and PGE2 in EMT of CRC cells in vitro. Methods: PGE2 and NAD+ levels, and immunoreactive 15-PGDH and COX-2 protein content, were measured in paired central and peripheral tissue from 20 CRCLM. 15-PGDH activity was measured by a [ 3 H]-PGE2 degradation assay in the presence or absence of exogenous NAD+ (1 μM). Parallel in vitro studies used a LIM1863 human CRC cell model of transforming growth factor (TGF) β-induced EMT and MCF-7 human breast cancer cells. Results: PGE2 levels were increased by a mean (95% CI) of 26% (1% to 52%) in the centre of CRCLM relative to peripheral tissue (mean 762 vs 604 pg/mg). Counter-intuitively, immunoreactive 15-PGDH protein levels were also increased (14% (3% to 27%)) in tumour centres, as was 15-PGDH activity in the presence of added NAD+ (16% (3% to 29%)). However, NAD+ levels were 59% (25% to 72%) lower in the centre of CRCLM than the periphery (mean 192 vs 546 pmol/mg) suggesting inefficient 15-PGDH-dependent catabolism may explain raised PGE2 levels. By contrast, there were no significant regional differences in immunoreactive COX-2 protein levels. In central areas of CRCLM, cancer cells exhibiting low E-cadherin expression had higher 15-PGDH expression than neighbouring E-cadherin-positive cells. Our CRCLM tissue observations were mirrored by LIM1863 cells undergoing EMT as hypoxic (1% O2) LIM1863 cells contained significantly less NAD+ and exhibited higher 15-PGDH protein levels than normoxic cells. 15-PGDH activity was significantly decreased in hypoxic MCF-7 cells compared with normoxic counterparts when NAD+ was present at a limiting concentration (no exogenous added). Furthermore, PGE2 (0.1–10 μM) promoted TGF-β-induced EMT in LIM 1863 cells in a concentration-dependent manner. Conclusion: Regional differences in PGE2 levels and 15-PGDH expression/activity are apparent in human CRCLM (possibly due to a hypoxic micro-environment). PGE2 promotes TGF-β-induced EMT in human CRC cells in vitro. Modulation of factors controlling PGE2 represents a novel therapeutic strategy against EMT in CRCLM.